Fabrication and characterization of a-Si micro and nano-gap structure for electrochemical sensor - Th Sabar, Dhahi; Uda, Hashim, Prof. Dr.; N. M., Ahmed; Md Eaqub, Ali (American Institute of Physics, 2012)
Link to publisher's homepage at http://proceedings.aip.org/